Perancangan Sistem Informasi Pengawasan Siswa Berbasis Android di SMKN 1 Ampek Angkek - Afrelia, Yutika; Okra, Riri; Efriyanti, Liza; Musril, Hari Antoni (Indonesian Research Journal on Education, 2023)
Supervision of students still uses the manual method, where students and teachers still use paper to record violations, achievements, and absenteeism. Designing an Android-Based Student Supervision Information System at SMKN 1 Ampek Angkek that is practical, effective, and efficient. The method used in this research is Research and Development or better known as (R&D), which is a method used to produce a system, with the system development model using the System Development Life Cycle (SDLC).The model used in this SDLC is the waterfall, namely Communication, Planning, Modeling, Construction, and Development. The product test used is the Validity Test, Effectiveness Test, and Practical Test. The system that has been designed has been tested and has been declared valid, effective, and practical in its use. Based on the results of the research that the researchers did, the researchers succeeded in making an android-based student supervision information system product at SMKN 1 Ampek Angkek. The results ofthe product test that the author did obtain a validity test from 3 experts obtained a value of 0.80 with a valid category, a practicality test from 4 practitioners obtained a value of 0.93 with a very high category, and the effectiveness test of 4 assessors obtained a value of 89% with effective category.